2017
DOI: 10.1016/j.brainres.2016.11.033
|View full text |Cite
|
Sign up to set email alerts
|

Representation of the body in the lateral striatum of the freely moving rat: Fast Spiking Interneurons respond to stimulation of individual body parts

Abstract: Numerous studies have shown that certain types of striatal interneurons play a crucial role in selection and regulation of striatal output. Striatal Fast-Spiking Interneurons (FSIs) are parvalbumin positive, GABAergic interneurons that constitute less than 1% of the total striatal population. It is becoming increasingly evident that these sparsely distributed neurons exert a strong inhibitory effect on Medium Spiny projection Neurons (MSNs). MSNs in lateral striatum receive direct synaptic input from regions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…No such result has ever been reported; on the contrary, specificity of phasic firing in relation to movement around an individual joint is similar between GPi and GPe neurons (Iansek & Porter, ; Erez et al ., ) and is lost only in disease models (Filion et al ., ; Rothblat & Schneider, ). We have recently suggested that, alternatively, maintaining low FR of MSNs that are unrelated to the current movement may involve striatal fast spiking interneurons that respond to individual body parts (Kulik et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…No such result has ever been reported; on the contrary, specificity of phasic firing in relation to movement around an individual joint is similar between GPi and GPe neurons (Iansek & Porter, ; Erez et al ., ) and is lost only in disease models (Filion et al ., ; Rothblat & Schneider, ). We have recently suggested that, alternatively, maintaining low FR of MSNs that are unrelated to the current movement may involve striatal fast spiking interneurons that respond to individual body parts (Kulik et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Coordinated FSI activity has proven hard to observe over long periods in vivo [14,118]. However, FSIs form local functional circuits [119], and in vivo, striatal FSI assemblies exhibit transient gap-junction dependent synchronization [66], possibly resulting from brief bouts of correlated cortical or homogeneous DAergic input. Furthermore, different subpopulations of FSIs have strong preferences for projecting to either D1 or D2 SPNs, as opposed to the overlapping projections modeled in our current study, and these distinct populations respond differently to cortical oscillations [80].…”
Section: Caveats and Limitationsmentioning
confidence: 99%
“…Nigrostriatal input exerts not only the classic receptor-dependent post-synaptic neuromodulation of MSN excitability (Gerfen and Surmeier, 2011), but also pre-synaptic inhibition of glutamate striatal release via dopaminergic receptors on corticostriatal terminals in an activity-dependent fashion (Bamford et al, 2004). MSN excitability is also influenced and modulated by striatal cholinergic and GABAergic interneurons (Tepper et al, 2004;Faust et al, 2016), which control striatal output activity particularly in the sensorimotor striatum (Kulik et al, 2017) and are also modulated by dopaminergic input (Momiyama and Nishijo, 2017). Altogether, corticostriatal and nigrostriatal axons interact at the synaptic level forming a functional unit with MSNs and interneurons (Shipp, 2017).…”
Section: Corticostriatal Organization and Functional Anatomymentioning
confidence: 99%